Digital Transformation of Services in Hospitals: The Role of Service Quality and Digital Readiness - Sebrina Erika Siahaan; Susanti Saragih (International Journal Labs, 2026)
Digital transformation in the health sector places the Hospital Management Information System as a strategic element in improving operational efficiency and service quality. However, the success of SIMRS implementation is not only determined by technical aspects, but also by the digital readiness of users. This research aims to analyze the determinants of the success of SIMRS implementation by integrating the Delone and McLean Information Systems success models and digital readiness variables as moderation. This study uses a quantitative approach with a survey method of 118 SIMRS users in several hospitals in the city of Bandung. Data were collected through an online questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that the quality of the system affects the net benefit through the end user of SIMRS, but not through user satisfaction. Meanwhile, information quality has the most consistent influence on net benefits both through SIMRS end-users and user satisfaction. The quality of service only affects the net benefit through user satisfaction, but not through the end user of SIMRS. In addition, digital readiness has been shown to strengthen the influence of system quality and information quality on the use of SIMRS, but does not moderate user satisfaction. These findings confirm that digital readiness strengthens technical system utilization, while user satisfaction is primarily driven by information quality and overall user experience. The study implies that hospital management should prioritize enhancing information quality, system reliability, and digital readiness of human resources to optimize SIMRS benefits